A Late Presentation of a Fatal Disease: Juvenile Hemochromatosis - Cynthia Cherfane; Pauline Lee; Leana Guerin; Kyle Brown (Case Reports in Medicine)
Juvenile hemochromatosis is a rare and severe form of hereditary hemochromatosis. We report the case of a 39-year-old female who presented with heart failure and cirrhosis from previously unrecognized juvenile hemochromatosis. This is the latest presentation described in the literature. An important clue to the diagnosis was a history of amenorrhea since the age of 20 that had never been investigated. The patient died of intractable heart failure two months after the initial presentation. Juvenile hemochromatosis should be suspected in a young patient with endocrine or cardiac manifestations. Early diagnosis is crucial since phlebotomy can improve the prognosis and delay or prevent progression to heart failure and cirrhosis.